The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s13765-015-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of rhizomicrobial isolates for phosphate solubilization and indole acetic acid production

Abstract: Recently, public concerns regarding the use of agrochemicals have increased due to the environmental impacts and potential risks to human health. The application of beneficial microorganisms is a novel technology to improve plant health and productivity and has therefore been extensively studied as an alternative strategy for biocontrol. In our study, 122 microbial isolates were obtained from the rhizosphere of Panax ginseng and subsequently tested in vitro for phosphate solubilization and indole acetic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Among the endophytic bacteria-induced growth promoting mechanisms resulting from plant hormones, IAA is the most common and extensively studied phytohormone. Recent studies have shown that more than 40% of all endophytic or rhizospheric bacteria are able to produce IAA (Palaniappan et al 2010;Li et al 2012;Andrade et al 2014;Hussein and Joo 2015), which is in agreement with our results (Fig. 2).…”
Section: Discussionsupporting
confidence: 93%
“…Among the endophytic bacteria-induced growth promoting mechanisms resulting from plant hormones, IAA is the most common and extensively studied phytohormone. Recent studies have shown that more than 40% of all endophytic or rhizospheric bacteria are able to produce IAA (Palaniappan et al 2010;Li et al 2012;Andrade et al 2014;Hussein and Joo 2015), which is in agreement with our results (Fig. 2).…”
Section: Discussionsupporting
confidence: 93%
“…In other words, carboxylic and hydroxylic anions produced by phosphate solubilizing bacteria have high calcium affinity and therefore can solubilize more phosphorus than acidification alone [44]. Accordingly, there is a symbiotic relationship between plants and phosphate solubilizing bacteria [45] [46], as bacteria provide the soluble phosphate and plant roots provide carbon compound such as sugars [47].…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms that strongly produce IAA were previously isolated from the rhizosphere of Panax schinseng (ginseng plant) South Korea [13]. The bacterial strain cultures were activated in Tryptic soy agar (TSA) medium, pH 7.2.…”
Section: Microorganisms and Inoculamentioning
confidence: 99%